Servicios de la cartera gerontológica social y el proceso de envejecimiento en los usuarios del Centro de Adulto Mayor Trujillo, 2021 - Abanto Meregildo, Nataly Nicoll (2023)
The present research was developed to analyze the influence of the services of the social gerontological portfolio in the aging process of the users of the Trujillo Senior Adult Center, Trujillo Province 2021, in which 50 older adults were sampled who participate in the activities and workshops carried out by the institution. In the research process, methods such as inductive - deductive, analytical - synthetic, and statistical were used, also resorted to the use of techniques such as interviews and surveys that made it possible to collect qualitative and quantitative information for the research to become much more complete. Likewise, instruments such as the questionnaire and the interview guide were used, with which it has been possible to describe the services of the social gerontological portfolio and the aging process of the users of the Trujillo Senior Center. The results obtained show that the services of the social gerontological portfolio positively influence the aging process of users, evidenced in the exercise of rights, the development of artistic abilities and physical skills, socialization, self-care, functionality, social participation, self-determination, and sense of belonging.